Preparation method of LDHs film on surface of magnesium alloy
By pre-treating magnesium alloys in an alkaline solution and performing a hydrothermal reaction with specific solutes, a dense LDHs nanosheet array is formed, addressing uneven density issues and improving corrosion resistance.
Patent Information
- Application Number
- CN202411276804.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-01-03
AI Technical Summary
Existing methods for preparing LDHs films on magnesium alloys result in uneven density and intersecting gaps, leading to reduced corrosion resistance, particularly in pitting sensitive regions.
A method involving pre-treatment of the magnesium alloy substrate in an alkaline mixed solution followed by a hydrothermal reaction in a precursor solution, using specific solutes like sodium bicarbonate and ethylenediaminetetraacetic acid to form dense nucleation points and stable metal cations, resulting in a dense LDHs nanosheet array structure.
The method achieves a high-density LDHs film with low porosity and enhanced corrosion resistance, particularly against pitting, through controlled nucleation and growth perpendicular to the substrate.
Smart Images

Figure HDA0005040435200000011 
Figure HDA0005040435200000012 
Figure HDA0005040435200000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnesium alloy surface treatment, and in particular relates to a method for preparing a LDHs film on the surface of a magnesium alloy. Background Art
[0002] The most common method for preparing LDHs films on the surface of magnesium alloys is the in-situ hydrothermal growth process, which is to place magnesium metal in a closed polytetrafluoroethylene-lined stainless steel container (autoclave) and subject it to high temperature (above 100°C) and pressure conditions. The in-situ growth of LDHs films strongly depends on the dissolution of the substrate, with the metal matrix acting as a source of one metal cation and the other metal ion coming from the growth solution. Therefore, the LDHs film grown directly on the surface of magnesium metal has a strong bond with the substrate. In addition, the thickness and microstructure of the film can be adjusted by controlling the chemical composition and microstructure of the magnesium alloy substrate, the composition of the growth solution (metal ion concentration and form, anion type, alkali source, etc.), and the hydrothermal conditions (reaction temperature and reaction time, solution pH, etc.). Generally, the microstructure and composition of the magnesium alloy substrate mainly affect the nucleation of LDHs, while the growth kinetics of LDHs can be regulated by adjusting the hydrothermal conditions. The in-situ hydrothermal method for preparing LDHs films has the advantages of simple operation, rich and diverse chemical composition and microstructure of LDHs, and high adhesion (chemical bonding) of the film layer.
[0003] However, without intervention, LDHs crystal growth is naturally random (determined by the surface state of the substrate). Therefore, based on the "competitive selectivity" growth process, LDHs tend to form intersecting lamellar structures with many intersecting gaps between the lamellar layers, which greatly reduces the density of the LDHs film and the gap size is uneven. For LDHs films used in metal corrosion protection, these LDHs intersecting gaps may interfere with or dominate the transmission path of corrosive substances, thereby leading to local aggregation of corrosive substances at the film / substrate interface, resulting in pitting sensitive "micro-regions".
[0004] Therefore, how to improve the density of LDHs film on the surface of magnesium alloy to increase the corrosion resistance of the treated magnesium alloy has become a research hotspot. Summary of the invention
[0005] The object of the present invention is to overcome the deficiencies of the above-mentioned prior art and to provide a method for preparing an LDHs film on the surface of a magnesium alloy having a high degree of densification and good pitting corrosion resistance.
[0006] To achieve the above object, in a first aspect of the present invention, the present invention provides a method for preparing a LDHs film on a magnesium alloy surface, the preparation method comprising the following steps:
[0007] (1) Pre-treating the magnesium alloy substrate;
[0008] (2) placing the magnesium alloy substrate pre-treated in step (1) in an alkaline mixed solution for immersion, and taking it out after the immersion is completed and drying it;
[0009] (3) placing the magnesium alloy substrate dried in step (2) in a precursor solution for hydrothermal reaction, taking it out after the hydrothermal reaction is completed, washing it, and drying it;
[0010] The solutes of the alkaline mixed solution include A and B, A is sodium bicarbonate, B is sodium hydroxide and / or potassium hydroxide, and the solvent is deionized water;
[0011] The precursor solution solutes include C and D, C is urea, D is ethylenediaminetetraacetic acid and / or sodium ethylenediaminetetraacetate, and the solvent is deionized water.
[0012] The present invention can obtain a dense LDHs nanosheet array structure membrane by pre-nucleating the pre-treated magnesium alloy substrate in an alkaline mixed solution and then performing a hydrothermal reaction in a precursor solution containing a specific solute. The obtained LDHs membrane has low porosity and excellent corrosion resistance.
[0013] Specifically, after the magnesium alloy substrate is polished and pre-treated, it is immersed in an alkaline mixed solution, wherein the solutes in the alkaline mixed solution are defined to include A and B, A is sodium bicarbonate, and B is sodium hydroxide and / or potassium hydroxide. The dissolved magnesium ions tend to be adsorbed and aggregated on the surface of the substrate rich in hydroxide (such as local concave and convex sites), thereby quickly forming dense crystal nucleus clusters on the magnesium alloy substrate; since the vertical orientation degree of the LDHs sheet depends largely on the density of the "active sites" or "seed crystals" on the substrate surface, therefore, the immersion in the alkaline mixed solution in the early stage can help the magnesium alloy substrate surface form dense nucleation points and LDHs crystal clusters. Then, the magnesium alloy substrate with dense nucleation points and LDHs crystal clusters is placed in a precursor solution of a specific solute, and ethylenediaminetetraacetic acid and / or sodium ethylenediaminetetraacetate provide stable and sufficient metal cation components for LDHs growth, which helps the rapid growth of LDHs microcrystals on the substrate, and tends to grow perpendicular to the substrate, thereby forming a dense array of LDHs films.
[0014] As a preferred embodiment of the preparation method of the present invention, the magnesium alloy includes any one of AZ31 and AZ91.
[0015] As a preferred embodiment of the preparation method of the present invention, in the alkaline mixed solution, the molar ratio of A to B is A:B=1:(10-25).
[0016] Illustratively, the molar ratio of A to B can be any point value or any range value between 1:(10-25), such as 1:10, 1:12, 1:14, 1:16, 1:18, 1:20, 1:22, 1:24, 1:25, etc.
[0017] As a preferred embodiment of the preparation method of the present invention, in the alkaline mixed solution, the molar concentration of A is 0.2-0.5 mol / L.
[0018] Illustratively, in the alkaline mixed solution, the molar concentration of A can be any point value or any two point range values between 0.2-0.5 mol / L, such as 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, etc.
[0019] The present invention has found that when the molar ratio of A to B in the alkaline mixed solution is further selected to be 1:(10-25) and the molar concentration of A is 0.2-0.5 mol / L, the LDHs film on the surface of the magnesium alloy obtained has a higher density and a stronger pitting corrosion resistance.
[0020] As a preferred embodiment of the preparation method of the present invention, the molar concentration of C in the precursor solution is 70-350 mmol / L.
[0021] As a preferred embodiment of the preparation method of the present invention, the molar concentration of D in the precursor solution is 10-50 mmol / L.
[0022] The present invention has found that when the molar concentrations of C and D in the precursor solution are further selected to be within the above-mentioned range, a good hexagonal lamellar LDHs structure can be formed, and the ab plane of the LDHs crystal sheet is perpendicular to the substrate. Most of the LDHs microcrystals grow evenly face to face into an array structure, and the gap spacing is reduced to the nanometer level. The obtained LDHs film has a higher density and better corrosion resistance.
[0023] As a preferred embodiment of the preparation method of the present invention, the pH value of the precursor solution is 8.5-10.5.
[0024] Preferably, the pH value of the precursor solution is adjusted by using an ammonia solution with a mass percentage of 1%.
[0025] Preferably, the precursor solution is prepared by adding C and D into boiled and cooled deionized water, and then adding an ammonia solution to adjust the pH value to 8.5-10.5.
[0026] As a preferred embodiment of the preparation method of the present invention, in the step (2), the immersion temperature is 60-80°C, and the immersion time is 4-10 hours.
[0027] Exemplarily, the immersion temperature can be any point value or any range value between 60-80°C, such as 60°C, 65°C, 70°C, 75°C, 80°C, etc.; the immersion time can be any point value or any range value between 4-10h, such as 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc.
[0028] The present invention has found that when the temperature and time of immersion in the alkaline mixed solution are within the above range, more nucleation points can be formed, which is more conducive to improving the density of LDHs crystal clusters, thereby helping to improve the density of the LDHs film.
[0029] As a preferred embodiment of the preparation method of the present invention, in the step (3), the temperature of the hydrothermal reaction is 100-125° C., and the time of the hydrothermal reaction is 12-24 h.
[0030] Exemplarily, the temperature of the hydrothermal reaction can be any point value or any two points in the range of 100-125°C, such as 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, etc.; the time of the hydrothermal reaction can be any point value or any two points in the range of 12-24h, such as 12h, 14h, 16h, 18h, 20h, 22h, 24h, etc.
[0031] The present invention has found that when the temperature and time of the hydrothermal reaction are selected within the above range, it is more conducive to the dense LDHs flakes tending to grow perpendicular to the substrate, thereby forming a dense array-like LDHs film.
[0032] Preferably, the hydrothermal reaction is a sealed reaction in a stainless steel autoclave containing a polytetrafluoroethylene liner.
[0033] As a preferred embodiment of the preparation method of the present invention, in the step (3), the drying temperature is 55-65° C., and the drying time is 1.5-2.5 h.
[0034] As a preferred embodiment of the preparation method of the present invention, in the step (1), the pretreatment includes mechanically polishing the magnesium alloy substrate using silicon carbide sandpaper, washing with ethanol and deionized water in sequence after polishing, and then air-drying.
[0035] Preferably, the mechanical polishing is performed using 600#, 1500# and 3000# silicon carbide sandpaper in sequence.
[0036] Preferably, the ethanol is an ethanol solution with a mass percentage of 95%.
[0037] As a preferred embodiment of the preparation method of the present invention, in the step (2), after taking out, the step of ultrasonic cleaning with deionized water is also included.
[0038] As a preferred embodiment of the preparation method of the present invention, in the step (3), washing is performed using boiled and cooled deionized water.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The present invention uses a magnesium alloy substrate to pre-nucleate in an alkaline mixed solution, and then performs a hydrothermal reaction in a precursor solution containing a specific solute, so as to obtain a dense LDHs nanosheet array structure membrane. The obtained LDHs membrane has low porosity and excellent corrosion resistance, especially pitting resistance. In addition, the preparation method provided by the present invention is simple to operate, has a wide range of raw material sources, and is conducive to actual production. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a SEM image of the magnesium alloy surface after treatment in step (1) in Example 1;
[0042] Figure 2 This is a SEM image of the magnesium alloy surface after treatment in step (2) in Example 1;
[0043] Figure 3 This is a SEM image of the magnesium alloy surface after treatment in step (3) in Example 1;
[0044] Figure 4 This is the SEM image of the magnesium alloy surface after treatment in Comparative Example 1;
[0045] Figure 5 This is the result obtained by using Image J image processing software to process the LDHs film on the surface of the magnesium alloy prepared in Example 1;
[0046] Figure 6 This is the result obtained by using Image J image processing software to process the LDHs film on the surface of the magnesium alloy prepared in Comparative Example 1;
[0047] Figure 7 This is the result obtained by using Image J image processing software to process the LDHs film on the surface of the magnesium alloy prepared in Comparative Example 4;
[0048] Figure 8 This is a comparison diagram of the anodic polarization curves of the LDHs film on the surface of the magnesium alloy prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0049] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0050] Unless otherwise specified, the reagents, methods and equipment used in the present invention are all conventional reagents, methods and equipment in the art; and unless otherwise specified, the raw materials used in parallel experiments are from the same batch of raw materials.
[0051] Example 1
[0052] The embodiment of the present invention provides a method for preparing a LDHs film on a magnesium alloy surface, the preparation method comprising the following steps:
[0053] (1) A magnesium alloy (AZ31) was mechanically polished with 600#, 1500#, and 3000# silicon carbide sandpapers in sequence, and then ultrasonically cleaned in 95% ethanol solution and deionized water in sequence. After cleaning, it was blown dry to obtain a pre-treated magnesium alloy substrate. The SEM image of the pre-treated magnesium alloy surface obtained at this time is as follows: Figure 1 As shown, from Figure 1 It can be seen that slight "scratches" appear on the surface of the magnesium alloy after mechanical polishing;
[0054] (2) The magnesium alloy substrate pretreated in step (1) was placed in an alkaline mixed solution (the alkaline mixed solution contained 2 mol / L sodium hydroxide, 0.2 mol / L sodium bicarbonate, and the solvent was deionized water) and immersed at 60° C. for 6 h; after the immersion, the substrate was taken out and ultrasonically cleaned with deionized water, and then dried; after drying, the magnesium alloy was observed for microscopic morphology, and the obtained SEM image was as shown in the following figure: Figure 2 As shown, from Figure 2 It can be seen that after step (2), hydroxide nanosheets (LDHs crystallites) are formed on the surface of the magnesium alloy;
[0055] (3) The magnesium alloy dried in step (2) was vertically immersed in a precursor solution (in the precursor solution, urea was 140 mmol / L, ethylenediaminetetraacetic acid was 10 mmol / L, the solvent was deionized water, and the pH value of the precursor solution was adjusted to 10 with a 1 wt % ammonia solution), and then the system was transferred to a stainless steel autoclave lined with tetrafluoroethylene, and then the autoclave was sealed and placed in an oven at 105° C. for 18 h for hydrothermal reaction; after the hydrothermal reaction was completed, the magnesium alloy was taken out and washed with boiled and cooled deionized water, and finally dried in an oven at 60° C. for 2 h; the surface micromorphology of the dried magnesium alloy was observed, and its SEM image was as shown in FIG. Figure 3 As shown, from Figure 3 It can be seen that the LDHs film formed on the surface of the magnesium alloy has a good hexagonal lamellar structure, and the ab plane is perpendicular to the substrate. Most of the LDHs crystallites grow evenly face to face (in parallel clusters) to form an array structure.
[0056] Example 2
[0057] The embodiment of the present invention provides a method for preparing a LDHs film on a magnesium alloy surface, the preparation method comprising the following steps:
[0058] (1) A magnesium alloy (AZ31) was mechanically polished with 600#, 1500#, and 3000# silicon carbide sandpaper in sequence, and then ultrasonically cleaned in 95% ethanol solution and deionized water in sequence, and then dried after cleaning to obtain a pre-treated magnesium alloy substrate;
[0059] (2) placing the magnesium alloy substrate pretreated in step (1) in an alkaline mixed solution (the alkaline mixed solution contains 5 mol / L potassium hydroxide, 0.5 mol / L sodium bicarbonate, and the solvent is deionized water) and immersing it at 80° C. for 4 h; after the immersion, taking it out and ultrasonically cleaning it with deionized water, and then drying it;
[0060] (3) The magnesium alloy dried in step (2) is vertically immersed in a precursor solution (in the precursor solution, urea is 350 mmol / L, sodium ethylenediaminetetraacetate is 50 mmol / L, the solvent is deionized water, and the pH value of the precursor solution is adjusted to 8.5 with 1 wt% ammonia solution), and then the system is transferred to a stainless steel autoclave lined with tetrafluoroethylene, and then the autoclave is sealed and placed in an oven at 125° C. for 12 h for hydrothermal reaction; after the hydrothermal reaction is completed, the magnesium alloy is taken out and washed with boiled and cooled deionized water, and finally dried in an oven at 60° C. for 2 h.
[0061] Example 3
[0062] The embodiment of the present invention provides a method for preparing an LDHs film on a magnesium alloy surface. The only difference between the preparation method and Example 1 is that in step (2), in the alkaline mixed solution, the sodium hydroxide is 10 mol / L, the sodium bicarbonate is 1 mol / L, and the solvent is deionized water.
[0063] Example 4
[0064] The embodiment of the present invention provides a method for preparing an LDHs film on a magnesium alloy surface. The only difference between the preparation method and Example 1 is that in step (2), in the alkaline mixed solution, the sodium hydroxide is 1 mol / L, the sodium bicarbonate is 0.1 mol / L, and the solvent is deionized water.
[0065] Example 5
[0066] The embodiment of the present invention provides a method for preparing an LDHs film on the surface of a magnesium alloy. The only difference between the preparation method and Example 1 is that in step (2), the immersion is performed at 90° C. for 6 hours.
[0067] Example 6
[0068] The embodiment of the present invention provides a method for preparing an LDHs film on the surface of a magnesium alloy. The only difference between the preparation method and Example 1 is that in step (2), the immersion is performed at 50° C. for 6 hours.
[0069] Example 7
[0070] The embodiment of the present invention provides a method for preparing an LDHs film on the surface of a magnesium alloy. The only difference between the preparation method and Example 1 is that in step (3), in the precursor solution, urea is 360 mmol / L, ethylenediaminetetraacetic acid is 60 mmol / L, the solvent is deionized water, and the pH value of the precursor solution is adjusted to 10 with 1 wt% ammonia solution.
[0071] Example 8
[0072] An embodiment of the present invention provides a method for preparing an LDHs film on a magnesium alloy surface. The only difference between the preparation method and Example 1 is that in step (3), in the precursor solution, urea is 50 mmol / L, ethylenediaminetetraacetic acid is 5 mmol / L, the solvent is deionized water, and the pH value of the precursor solution is adjusted to 10 with a 1 wt% ammonia solution.
[0073] Example 9
[0074] The embodiment of the present invention provides a method for preparing an LDHs film on the surface of a magnesium alloy. The only difference between the preparation method and Example 1 is that in step (3), the hydrothermal reaction is carried out at 135° C. for 12 hours.
[0075] Example 10
[0076] The embodiment of the present invention provides a method for preparing an LDHs film on the surface of a magnesium alloy. The only difference between the preparation method and Example 1 is that in step (3), the hydrothermal reaction is carried out at 90° C. for 12 hours.
[0077] Comparative Example 1
[0078] The comparative example of the present invention provides a method for preparing a LDHs film on the surface of a magnesium alloy. The only difference between the preparation method and Example 1 is that there is no step (2);
[0079] The microscopic morphology of the magnesium alloy after hydrothermal growth, washing and drying was observed. The SEM images obtained are as follows: Figure 4 As shown, from Figure 4 It can be seen that a typical cross-linked LDHs thin film with obvious gaps grows on the surface of the magnesium alloy.
[0080] Comparative Example 2
[0081] The comparative example of the present invention provides a method for preparing an LDHs film on the surface of a magnesium alloy. The only difference between the preparation method and Example 1 is that in step (2), the sodium hydroxide in the alkaline mixed solution is 2.2 mol / L and the solvent is deionized water.
[0082] Comparative Example 3
[0083] The comparative example of the present invention provides a method for preparing an LDHs film on the surface of a magnesium alloy. The only difference between the preparation method and Example 1 is that in step (2), the sodium bicarbonate in the alkaline mixed solution is 2.2 mol / L and the solvent is deionized water.
[0084] Comparative Example 4
[0085] The comparative example of the present invention provides a method for preparing a LDHs film on the surface of a magnesium alloy, and the preparation method comprises the following steps:
[0086] (1) A magnesium alloy (AZ31) was mechanically polished with 800#, 1500#, and 2000# silicon carbide sandpaper in sequence, and then ultrasonically cleaned in deionized water. After cleaning, it was blown dry to obtain a pre-treated magnesium alloy substrate;
[0087] (2) placing the magnesium alloy substrate pretreated in step (1) in an alkaline mixed solution (the alkaline mixed solution contains 2 mol / L sodium hydroxide and the solvent is deionized water) and immersing it at 60° C. for 4 h; after the immersion, taking it out and ultrasonically cleaning it with deionized water, and then drying it;
[0088] (3) The magnesium alloy dried in step (2) is vertically immersed in a precursor solution (in the precursor solution, urea is 20 mmol / L, sodium ethylenediaminetetraacetate is 50 mmol / L, and ferric nitrate nonahydrate is 20 mmol / L, the solvent is deionized water, and the pH value of the precursor solution is adjusted to 10 with 1 wt% ammonia solution), and then the system is transferred to a stainless steel autoclave lined with tetrafluoroethylene, and then the autoclave is sealed and placed in an oven at 105°C for 6 hours for hydrothermal reaction; after the hydrothermal reaction is completed, the magnesium alloy is taken out and washed with boiled and cooled deionized water, and finally dried in an oven at 60°C for 2 hours.
[0089] Effect example
[0090] Effect Examples of the Invention The performance of the LDHs film on the surface of the magnesium alloy prepared in the examples and comparative examples is investigated, including the following aspects:
[0091] 1. Porosity of LDHs film on magnesium alloy surface: According to the SEM microscopic morphology of LDHs film on magnesium alloy surface prepared in the embodiment and comparative example, the obtained LDHs film morphology is imported into Image J image processing software to set a fixed image area, and the proportion of pore area is calculated to obtain the porosity of the sample;
[0092] 2. Pitting resistance: The LDHs film samples on the magnesium alloy surface prepared in the examples and comparative examples were used as anodes, platinum electrodes as cathodes, and calomel electrodes as reference electrodes. Anode polarization electrochemical tests were performed using an electrochemical workstation to obtain the anode polarization curves and record the turning point E of the sudden increase in the anode branch corrosion current. pit (pitting point);
[0093] The obtained results are shown in Table 1;
[0094] Table 1
[0095] Porosity <![CDATA[E pit / V]]> Porosity <![CDATA[E pit / V]]> Example 1 0.1723 0.20 Example 8 0.1837 0.18 Example 2 0.1814 0.18 Example 9 0.1935 0.18 Example 3 0.1954 0.17 Example 10 0.1941 0.17 Example 4 0.1987 0.18 Comparative Example 1 0.6621 -0.12 Example 5 0.1904 0.17 Comparative Example 2 0.5936 0.03 Example 6 0.1979 0.18 Comparative Example 3 0.6321 0.02 Example 7 0.1868 0.19 Comparative Example 4 0.2268 0.12
[0096] It can be seen from Table 1 that the porosity of the LDHs film on the surface of the magnesium alloy prepared by the preparation method of the present invention is low, below 0.1987, and the pitting corrosion resistance is high. pit The positive offset value is above 0.17V;
[0097] The SEM microscopic morphology of the LDHs film on the magnesium alloy surface prepared in Example 1, and the data obtained by using Image J image processing software are as follows: Figure 5 As shown, the data obtained by using Image J image processing software to process the LDHs film on the surface of the magnesium alloy prepared in Comparative Example 1 are as follows: Figure 6 As shown, the data obtained by using Image J image processing software to process the LDHs film on the surface of the magnesium alloy prepared in Comparative Example 4 are as follows: Figure 7 As shown, the comparison of the anodic polarization curves of the LDHs film on the magnesium alloy surface prepared in Example 1 and Comparative Example 1 is shown in Figure 8 shown; from Figure 8 It can also be clearly seen that the LDHs film on the surface of the magnesium alloy obtained by the preparation method of the present invention has a stronger pitting corrosion resistance.
[0098] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a LDHs film on a magnesium alloy surface, characterized in that: The preparation method comprises the following steps: (1) Pre-treating the magnesium alloy substrate; (2) placing the magnesium alloy substrate pre-treated in step (1) in an alkaline mixed solution for immersion, and taking it out after the immersion is completed and drying it; (3) placing the magnesium alloy substrate dried in step (2) in a precursor solution for hydrothermal reaction, taking it out after the hydrothermal reaction is completed, washing it, and drying it; The solutes of the alkaline mixed solution include A and B, A is sodium bicarbonate, B is sodium hydroxide and / or potassium hydroxide, and the solvent is deionized water; The precursor solution solutes include C and D, C is urea, D is ethylenediaminetetraacetic acid and / or sodium ethylenediaminetetraacetate, and the solvent is deionized water.
2. The preparation method according to claim 1, characterized in that: In the alkaline mixed solution, the molar ratio of A to B is A:B=1:(10-25).
3. The preparation method according to claim 1, characterized in that: In the alkaline mixed solution, the molar concentration of A is 0.2-0.5 mol / L.
4. The preparation method according to claim 1, characterized in that: In the precursor solution, the molar concentration of C is 70-350 mmol / L.
5. The preparation method according to claim 1, characterized in that: In the precursor solution, the molar concentration of D is 10-50 mmol / L.
6. The preparation method according to claim 1, characterized in that: The pH value of the precursor solution is 8.5-10.
5.
7. The preparation method according to claim 1, characterized in that: In the step (2), the immersion temperature is 60-80° C. and the immersion time is 4-10 h.
8. The preparation method according to claim 1, characterized in that: In the step (3), the temperature of the hydrothermal reaction is 100-125° C., and the time of the hydrothermal reaction is 12-24 hours.
9. The preparation method according to claim 1, characterized in that: In the step (3), the drying temperature is 55-65° C. and the drying time is 1.5-2.5 h.
10. The preparation method according to claim 1, characterized in that: In the step (1), the pretreatment includes mechanically polishing the magnesium alloy substrate using silicon carbide sandpaper, washing with ethanol and deionized water in sequence after polishing, and then drying.